Use of a cloud‐based search engine of a centralized donor database to identify historical antigen‐negative units in hospital inventories. Issue 2 (5th January 2020) - Denomme, Gregory A.; Reinders, Steve; Bensing, Kathleen M.; Piefer, Cindy; Schanen, Michael; Curnes, Jennifer; Treml, Angela; Gottschall, Jerome L.; Anani, Waseem Q.
Abstract : BACKGROUND: The provision of units with antigen‐negative attributes is required for alloimmunized transfusion recipients and to avoid alloimmunization among patients on chronic transfusion support. Recent evidence confirms that the demand for antigen‐typed units is increasing. STUDY DESIGN AND METHODS: A cloud‐based search engine was designed by the blood center to find antigen‐negative units. The service provided access to historical antigen information for units in hospital inventories. The hospital transfusion service was required to confirm the antigen phenotype. The results of 16 hospitalsʼ use over 5 years were analyzed to determine trends and value of the service. The time commitment of the cloud‐based query was compared to the hospital performing manual phenotyping with an outcome of at least one unit found with the desired antigen‐negative attribute(s). RESULTS: Hospitals were located between 4 miles and 200 miles away from the blood center. A total of 6, 081 queries were submitted over the 5 years, with an overall 50% success rate of finding at least one unit. Single antigen queries accounted for 67% of total searches, with two antigen queries and three or more antigen queries accounting for 24% and 9% of the units found, respectively. The cloud‐based antigen query was most efficient for combined antigen frequencies <0.5 for two or more antigen‐negative attributes. CONCLUSION: A cloud‐based search engine provides hospitals with access to historical antigen information housed at the blood center. Future refinements may consider regulatory submission of a process to provide confirmed historical information through this cloud‐based program.